Scope of the Element of Trick in Arbitration Board Decisions in Indonesia - Sijabat, Joshua Narwastu; Kamello, Tan; Sembiring, Rosnidar; Nasution, Abdul Haris (IHSA Institute, 2024)
This study aims to determine the scope of the element of deception in the cancellation of arbitration decisions after the Constitutional Court Decision No. 15/PUU-XII/2014. The type of research used in this study is normative legal research (normative juridical). The nature of the research is descriptive, which explains how to study problems in society, develop concepts, collect facts, but does not test hypotheses. The type of data used is secondary data in the form of legal materials. Legal materials are in the form of primary legal materials and secondary legal materials. Primary legal materials are authoritative legal materials. While secondary legal materials are in the form of all publications on law including textbooks, legal dictionaries, legal journals and comments on court decisions. By limiting the scope of the element of deception in the cancellation of arbitration decisions, it can provide justice for the disputing parties